ANALISIS INDEKS KEPUASAN MASYARAKAT TERHADAP PELAYANAN PUBLIK PADA UPTD PUSKEMAS SENTANI KOTA - Nurjaman, Rahmat; Songubun, Starla Lorenza (Fakultas Kedokteran Universitas Jenderal Soedirman, 2024)
This research aims to determine and analyze the Community Satisfaction Index with Public Services at the Sentani City Health Center UPTD. This research is a type of descriptive research that uses Community Satisfaction Index (IKM) analysis. The population used in this research is all people who are receiving services at the Sentani City Community Health Center. The sample will be taken as many as 100 people from service users in April and May using a sampling technique, namely the Non-Probability sampling technique with accidental sampling type. Data collection techniques use observation, documentation and questionnaires. Processing and analyzing research data uses the Descriptive Statistical Analysis method. The results of research on the Community Satisfaction Index with Public Services at the UPTD Puskesmas Sentani Kota, based on the guidelines of the Regulation of the Minister for Empowerment of State Apparatus and Indonesian Bureaucratic Reform Number 14 of 2017 concerning guidelines for compiling Community Satisfaction Surveys have gone well. Where the results of the Community Satisfaction Index are obtained are seen from 9 indicators with IKM conversion value= ∑Weighted NRR × 25 (Conversion Value 3.271 × 25 = 81.79 with service quality